1981
DOI: 10.1177/002199838101500404
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between Engineering Properties and Delamination of Composite Materials

Abstract: The dispersion of harmonic waves propagating in an arbitrary direction in a layered orthotropic elastic composite is studied. The full three-dimensional field equations of elasticity are considered, and the corresponding twelfth order characteristic determinant is examined. Numerical results are obtained and compared with the corresponding estimates of the new quotient method of Nemat-Nasser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(48 citation statements)
references
References 17 publications
5
43
0
Order By: Relevance
“…It is shown that the strength of a composite is strongly dependent on its stacking sequence [24,25]. For unidirectional continuous carbon/glass fibre-reinforced hybrid composites under flexural loading, it was shown that partial substitution of glass fibres for carbon fibres on the compressive face resulted in improved flexural strength, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the strength of a composite is strongly dependent on its stacking sequence [24,25]. For unidirectional continuous carbon/glass fibre-reinforced hybrid composites under flexural loading, it was shown that partial substitution of glass fibres for carbon fibres on the compressive face resulted in improved flexural strength, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…10). More delamination was present in the 10 0 specimen in which the mismatch in coefficient of mutual influence is largest [9]. The alternating 45 1 specimens failed in a mode similar to the clustered laminate (Fig.…”
Section: Failure Mechanismsmentioning
confidence: 88%
“…The influence of interlaminar stresses on the prediction of initial failure using the tensor polynomial failure criterion was considered by this author and his colleagues in two previous papers [6,7] where it was shown that the interlaminar shear stress TZx dominates the initiation of failure in graphite-epoxy for fiber angles smaller than 370. The relationship between engineering properties and delamination of finite-width graphite-epoxy laminates was recently studied by this author [9]. It was shown that there is a close correspondence between the mismatch in coefficient of mutual influence of adjacent layers and delamination of angle-ply laminates.…”
Section: Introductionmentioning
confidence: 97%
“…Interlaminar shear stresses (zxz) have been shown to vary qualitatively with the magnitude of mis-match in the 'coefficient of mutual influence' between adjacent layers, which can be reduced by altering the stacking sequence [8]. Similarly, the interlaminar normal stress (az) at any interface varies with the magnitude of the moment due to cry of the lamina about the laminate surface.…”
Section: Laminates: Stacking Sequencementioning
confidence: 99%
“…Herakovich [8] performed a finite element analysis to determine the distribution of interlaminar shear stresses for various stacking sequences of a (0/+ 45/90) laminate and observed that the resistance to delamintion varied with the various stacking sequences.…”
Section: Laminates: Stacking Sequencementioning
confidence: 99%